Studies on the biology of the scads, Decapterus russelli and Decapterus macrosoma at Vizhinjam, southwest coast of India - Balasubrahmanian, N K; Natarajan, P (Indian Journal of Fisheries, 2011)
Predominant among carangids, the scads Decapterus russelli and Decapterus macrosoma, though showed female domination, did not show any significant divergence in sex ratio. Both the species were found to breed continuously with two peak spawning seasons. While March to May and November to December were the periods for D. russelli, the same were between February, June, October and December in D. macrosoma. When D. russelli males and females attained first maturity at age 0.91 years (150 and 140 mm total length respectively), D. macrosoma species attained maturity on reaching 1.05 years (male 158 mm and females 157 mm). The regression coefficient and Y-intercept of the logarithmic length-weight relationship were 2.9251; -1.8668 and 3.46231; -3.1139 respectively for D. russelli and D. macrosoma. The ELEFAN analysis showed L<Â» and K values for the two species in the above order as 290 mm; 0.8y’ and 257 mm; O.By’. The von Bertalanffy plot estimated t, values as -0.044 and -0.0215 respectively. In the two recruitment pulses observed in both species, June-July and February corresponded to the peaks in the case of D. russeli, the same in D. macrosoma being May and August.